The African (AU) human rights agenda : the panacea to the problem of non-compliance with human rights norms in Africa? - Oloka-Onyango, J. (University of Pretoria, 2006)
Prepared under the supervision of Prof. J. Oloka-Onyango, Faculty of Law, Makerere University